The Cartojuridism of the British East India Company - Suresh, Sabarish (Law and history review, 2024)
This paper will engage with the early colonial maps of the British East India Company to analyze its representative, as well as creative, functions, delineating how maps represent existing legal relations, entrench hierarchies, and visually transmit projected, and aspired, notions of legal authority and sovereignty. This paper studies the constitutive role of cartography apropos law, territory, and social order, in a specific historical context, by examining the crucial political role played by the British East India Company's cartographic practices and maps in aspiring and imagining the transplantation and establishment of English sovereignty in the Indian subcontinent. This paper will also show how British maps visually entrenched and supplemented unique forms of social hierarchy and marginalization, and legal categories and stratifications, in Indian cities. By analyzing maps, memoirs, cartouches, dedications, ornaments, plans, prospects, and historical manuscripts appertaining to the eighteenth and early nineteenth century operations of the Company, this paper will demonstrate, firstly, that cartography preceded, visually imagined, and set the stage for the coalescence of British sovereignty and the expansion of its law in the Indian subcontinent; secondly, that cartography provided the visual support for social ordering; and thirdly, that maps do not have a singular function. This paper proposes a notion of cartojuridism to capture the myriad ways in which cartography, law, sovereignty, and society intersect and relate with each other.